Revenge of the roach! - Doodler, Todd H. (Doodler, Todd H. Super Fly., 2016)
When Crazy Cockroach and two dung beetle henchmen try to brainwash the children of Stinkopolis using video games, only Super Fly and his sidekick, Fantastic Flea, can stop them.